Preserving the unique legacy of SM Idris - Abdul Razak, Dzulkifli (Sun Media Corporation Sdn Bhd, 2019)
THERE is an old African proverb that says when a wise person dies, a whole library is burnt down. There can never be a better illustration of this than the recent demise of the legendary consumer-environment-‎people’s (the list goes on) advocate, the late SM Mohamed Idris (1926-2019), fondly known as “uncle”.